Initial peptidomic profiling of Brazilian sea urchins: Arbacia lixula, Lytechinus variegatus and Echinometra lucunter. Issue 1 (December 2016) - Sciani, Juliana; Emerenciano, Andrews; Cunha da Silva, José; Pimenta, Daniel
Abstract Background Sea urchins can be found throughout the Brazilian coast and are reported to be one of the major causes of marine accidents on the shoreline. Although not lethal, these accidents are reported to be extremely painful. In order to understand the toxinology of the Brazilian urchins, a peptidomic approach was performed aiming to characterize the naturally occurring peptides in both the coelomic fluid and the spine. Methods Animals were collected without gender distinction and samples of the coelomic fluid and spines extracted were analyzed by RP-HPLC and mass spectrometry for peptidede novo sequencing. Results Several peptides were identified either in the coelomic fluid or the spine extract (except forE. lucunter ). The peptide sequences were aligned with public deposited sequences and possible functions were inferred. Moreover, some peptides can be cryptides, since their sequences were identified within functional proteins, for example thymosin fromStrongylocentrotus purpuratus. Conclusions Although preliminary, the peptidomic approach presented here reports, for the first time, the abundance of novel biological molecules derived from these animals. The discovery of such molecules may be of potential biotechnological application, as described for other organisms; nevertheless, further studies are required.